Cyro Martins : os anos decisivos (1908-1951) - Nascimento, Fábio Varela (2018)
Cyro Martins – os anos decisivos (1908-1951) is a biographical work, which aims to tell part of the life of the doctor, psychoanalyst and writer Cyro dos Santos Martins, born in Quaraí on August 5, 1908 and deceased in Porto Alegre on December 15, 1995. In these decisive years are the beginning of the formation, the years spent as an internal student of the Colégio Anchieta, the period in the Faculdade de Medicina de Porto Alegre, the return to Quaraí, the loss of the father, the first marriage, the specialization in neurology in Rio de Janeiro, the publication of five books – Campo fora (1934), Sem rumo (1937), Enquanto as águas correm (1939), Mensagem errante (1942), Porteira fechada (1944) –, collaborations in the press, insertion in the literary system of Rio Grande do Sul, as an employee in the Hospital Psiquiátrico São Pedro, the birth of daughters, separation, second marriage and departure for Buenos Aires. The study also contemplates, at an initial moment, considerations about the biographical genre – theorists such as Leon Edel, Anna Caballé and François Dosse are cited – , elucidates the relationship between the biographer and the biographer, explains the methods used and indicates the spaces of research.